Imaging homeostatic sleep pressure and circadian rhythm in the human brain - Fang, Zhuo; Rao, Hengyi (Journal of Thoracic Disease; Vol 9, No 5 (May 28, 2017): Journal of Thoracic Disease, 2017)
It is well-known that our sleep-wake patterns and alertness level during wakefulness are mainly modulated by two interactive processes, a homeostatic sleep debt process (S) refers to the drive for sleep that increases as a saturating exponential when we stay awake and decreases exponentially when we sleep, and a circadian processes (C) refers to the internal oscillatory rhythm that runs about 24 hours and can be reset by the environmental light (1-3).